Imaging the distribution of iron oxide nanoparticles in hypothermic perfused tissues. Issue 5 (9th December 2019) - Ring, Hattie L.; Gao, Zhe; Sharma, Anirudh; Han, Zonghu; Lee, Charles; Brockbank, Kelvin G. M.; Greene, Elizabeth D.; Helke, Kristi L.; Chen, Zhen; Campbell, Lia H.; Weegman, Bradley; Davis, Monica; et al.
Abstract : Purpose: Herein, we evaluate the use of MRI as a tool for assessing iron oxide nanoparticle (IONP) distribution within IONP perfused organs and vascularized composite allografts (VCAs) (i.e., hindlimbs) prepared for cryopreservation. Methods: Magnetic resonance imaging was performed on room‐temperature organs and VCAs perfused with IONPs and were assessed at 9.4 T. Quantitative T1 mapping and T 2 ∗ ‐weighted images were acquired using sweep imaging with Fourier transformation and gradient‐echo sequences, respectively. Verification of IONP localization was performed through histological assessment and microcomputer tomography. Results: Quantitative imaging was achieved for organs and VCAs perfused with up to 642 mMFe (36 mgFe /mL), which is above previous demonstrations of upper limit detection in agarose (35.7mMFe [2 mgFe /mL]). The stability of IONPs in the perfusate had an effect on the quality of distribution and imaging within organs or VCA. Finally, MRI provided more accurate IONP localization than Prussian blue histological staining in this system, wherein IONPs remain primarily in the vasculature. Conclusion: Using MRI, we were able to assess the distribution of IONPs throughout organs and VCAs varying in complexity. Additional studies are necessary to better understand this system and validate the calibration between T1 measurements and IONP concentration.